KAJIAN KRITIS TERHADAP EKSISTENSI BANK TANAH DALAM UNDANG-UNDANG NO. 11 TAHUN 2020 TENTANG CIPTA KERJA - Nizam Arrizal; Siti Wulandari (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
This research examines the existence of a Land Bank which was established based on law number 11 of 2020 concerning Job Creation which gets the pros and cons of the community, activists, and academics. Land as a gift from God Almighty is controlled by the State and used as much as possible for the prosperity of the people. The legal issue discussed in this study is the urgency of establishing a land bank and the role and function of the Land Bank as a land management institution. The method used is a normative juridical research method, namely research on legal principles using secondary data. The data analysis method used was qualitative methods and the data collection tool used was document study. The result of this research is that the presence of a land bank is very much needed by the community and government in the management and arrangement of land for the public interest and residence. The role and function of a land bank is an institution that manages land by carrying out the planning, acquisition, procurement, management, utilization and distribution of land